Comparative genomic analysis of pleurotus species reveals insights into the evolution and coniferous utilization of Pleurotus placentodes - Sun, Lei; Yin, Xiaolei; Sossah, Frederick Leo; Han, Xuerong; Li, Yu (Frontiers in Molecular Biosciences, 2023)
Pleurotus placentodes (PPL) and Pleurotus cystidiosus (PCY) are economically valuable species. PPL grows on conifers, while PCY grows on broad-leaved trees. To reveal the genetic mechanism behind PPL's adaptability to conifers, we performed de novo genome sequencing and comparative analysis of PPL and PCY. We determined the size of the genomes for PPL and PCY to be 36.12 Mb and 42.74 Mb, respectively, and found that they contain 10,851 and 15,673 protein-coding genes, accounting for 59.34% and 53.70% of their respective genome sizes. Evolution analysis showed PPL was closely related to P. ostreatus with the divergence time of 62.7 MYA, while PCY was distantly related to other Pleurotus species with the divergence time of 111.7 MYA. Comparative analysis of carbohydrate-active enzymes (CAZYmes) in PPL and PCY showed that the increase number of CAZYmes related to pectin and cellulose degradation (e.g. AA9, PL1) in PPL may be important for the degradation and colonization of conifers. In addition, geraniol degradation and peroxisome pathways identified by comparative genomes should be another factors for PPL's tolerance to conifer substrate. Our research provides valuable genomes for Pleurotus species and sheds light on the genetic mechanism of PPL's conifer adaptability, which could aid in breeding new Pleurotus varieties for coniferous utilization.